2020
DOI: 10.1111/tmi.13532
|View full text |Cite
|
Sign up to set email alerts
|

The impact of HIV on hepatocellular cancer survival in Nigeria

Abstract: Background Hepatocellular carcinoma (HCC) is an increasing cause of mortality in HIV‐infected individuals. We compared host and tumour characteristics between HIV‐infected and HIV‐uninfected Nigerians with HCC and examined the impact of HIV on survival. Methods This prospective observational study was conducted at Jos University Teaching Hospital in Jos, Nigeria, among adults (>18 years) with HCC enrolled between September 2015 and September 2017 and followed until April 2019. Demographics, tumour characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…HBV was also highly prevalent in this cohort (52%), a finding not unexpected since Nigeria is a region that is considered hyperendemic for HBV, with high rates of infection in those with and without HIV (9.9%-13.2%) [ 39 ]. Previous studies have found HBV in over 60% of persons with HCC in Nigeria, similar to our data [ 11 ]. In studies from Asia, both high HBV serum DNA levels and HBeAg seropositivity have been shown to correlate with more advanced HCC disease (portal vein tumor thrombosis and extrahepatic metastases) as well as a higher mortality [ 40 ].…”
Section: Discussionsupporting
confidence: 92%
“…HBV was also highly prevalent in this cohort (52%), a finding not unexpected since Nigeria is a region that is considered hyperendemic for HBV, with high rates of infection in those with and without HIV (9.9%-13.2%) [ 39 ]. Previous studies have found HBV in over 60% of persons with HCC in Nigeria, similar to our data [ 11 ]. In studies from Asia, both high HBV serum DNA levels and HBeAg seropositivity have been shown to correlate with more advanced HCC disease (portal vein tumor thrombosis and extrahepatic metastases) as well as a higher mortality [ 40 ].…”
Section: Discussionsupporting
confidence: 92%
“…A study from Mozambique found that 18% of HCC patients (34 cases) enrolled were infected with HIV, and the majority of these patients (68%) were coinfected with HBV. In addition, HCC presented early in HIV-HBV coinfected patients compared to HIV negative individuals [56] . A study from South Africa demonstrated that females with HIV-HBV coinfection present at a younger age (36 years) compared to HBV mono-infected women (50 years); more importantly, the HIV-infected patients had a lower median survival (82 days) compared to patients without HIV (181 days) [10] .…”
Section: Hcc In Hiv-hbv Coinfected Patients In Africamentioning
confidence: 94%
“…A study from South Africa demonstrated that females with HIV-HBV coinfection present at a younger age (36 years) compared to HBV mono-infected women (50 years); more importantly, the HIV-infected patients had a lower median survival (82 days) compared to patients without HIV (181 days) [ 10 ] . Similarly, a prospective study carried out in a Hospital in Nigeria, showed that most patients with HIV and HCC were HBsAg positive, and at three months, the chances of survival in HIV-infected and HIV-uninfected individuals were 22% and 47%, respectively [ 57 ] . A recent report from Ethiopia by Tassachew et al .…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
“…In fact, it is known that HIV-positive patients arrive at the diagnosis of HCC at a younger age in an intermediate-advanced stage compared to the general population and that they have a clinically more aggressive course—reasons that restrict the choice of practicable therapeutic options [ 35 , 36 ]. Closer surveillance of HCC would therefore be largely warranted in HIV-positive patients to increase the chances of a better outcome [ 11 ], particularly if co-infected with HBV [ 37 ]. Furthermore, a low percentage of HIV patients adhere to cancer screening programs, often not sufficiently promoted by the doctor as a mandatory part of the patient’s clinical management [ 12 , 38 ].…”
Section: Screening and Diagnosismentioning
confidence: 99%
“…In PLWH HCC nearly always reveals itself at an advanced stage of disease with limited therapeutical possibilities [ 66 , 67 ]. In most cases, HCC has a faster clinical presentation in PLWH and at a younger age than the general population, resulting in a shorter survival [ 34 , 37 , 68 ]. Furthermore, the overall mortality in patients with both HIV and cancer was significantly higher than expected on the basis of mortality rates for each disease separately [ 69 ].…”
Section: Hcc In Hiv Patientsmentioning
confidence: 99%